Case report: Anesthesia management for surgical treatment of glucagonoma with symptom of characterized necrolytic migratory erythema - Xia, Di; Shen, Le (Frontiers in Oncology, 2024)
BackgroundThe anesthetic management of patients with glucagonoma is complicated by a number of factors including glucose fluctuation, characterized necrolytic migratory erythema in oral and pharyngeal, which may lead to an unexpected difficult airway.Case presentationHerein we describe the anesthetic considerations and management of a 47-year-old adult with glucagonoma, who presented for a laparoscopic splenectomy and distal pancreatectomy procedure.ConclusionThis report details fiberoptic intubation in an adult with glucagonoma and necrolytic migratory erythema. We recommend that this approach be considered in patients with glucagonoma and severe necrolytic migratory erythema undergoing general anesthesia.